Incorporación de materia orgánica y su efecto en el comportamiento agronómico del cultivo de maíz (Zea mays l), en la zona de Babahoyo. - León Alemán, Oswaldo Vladimir (2019)
. SUMMARY The present experimental work was carried out in the premises of the Experimental Farm "San Pablo" belonging to the Technical University of Babahoyo, it is located at km 1.5 via Babahoyo-Montalvo. Twelve treatments and three repetitions were investigated. The objective of the research was to design the application of organic matter in the production of corn crops. The sowing of corn was done with the DAS-3385 varieties in experimental units of 9 m2. The treatments were distributed in a randomized complete block design. The evaluation of means was made with the Tukey test at 5% significance. The evaluated variables were: Height of the plants, Height of insertion in the first ear, Days of male flowering, Day of harvest, Length of ears of corn, Number of ears per plant, Weight of 100 grains, Yield per hectare, Economic analysis and of Soils. The results are found in this experimental work, it is shown that the application of organic matter is an alternative for increasing the yield of corn crop, and that grain production is maximized. The highest yield of the crop (13482.15 kg / ha) was presented applying Humus 2000 kg / ha. Keywords: organic matter; Ground; Corn; effect; production